Analisis Pengaruh Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Pada Rumah Sakit Muhammadiyah Palembang - Gumar Herudiansyah; Mister Candera; Kevin Haminsyah (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2020)
This study aims to analyze the effect of the dimensions of health service quality on the level of patient satisfaction at the Muhammadiyah Hospital in Palembang. This type of research is quantitative research. The study population was patients at Muhammadiyah Hospital Palembang. The sample is determined by the convenience sampling method, with 100 respondents. The data collection method used was a questionnaire (questionnaire) technique. Data analysis method used is multiple linear analysis method. In the research results obtained using SPSS, showing the results of the t test that shows that tangible variables, responsiveness, reliability, assurance and empathy have a significant effect on patient satisfaction. The results of the f test of tangible variables, responsiveness, reliability, assurance and empathy simultaneously have a significant effect on patient satisfaction at Muhammadiyah Hospital Palembang.